Krisis Identitas Nasional Pada Generasi Muda di Era Globalisasi - Rahmi Rahmi; Saniyyah Salwa Nabiilah; Sasmi Nelwati (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Generation tends to be more interested in foreign cultures than their own national culture, especially among students. Many foreign cultures have entered and flourished among the community, particularly the younger generation. This situation threatens and endangers national identity if left unchecked. A national identity crisis can occur, especially among the younger generation, particularly students, who are highly susceptible to the influences of globalization. Therefore, there is a need for awareness to preserve cultural values as national identity is increasingly fading. Additionally, there is a necessity for methods or actions to enhance the awareness of the younger generation, especially students, towards national identity while also considering the advancements in science, technology (IPTEK) in today's era.